2021
DOI: 10.17648/acta.scientiae.6552
|View full text |Cite
|
Sign up to set email alerts
|

Prospective high school mathematics teachers’ assessment of the epistemic suitability of a proportionality textbook lesson

Abstract: Background: Every teacher should be able to use curriculum materials to guide instructional design and make reasoned pedagogical decisions about the limitations these resources may have. Objectives: In this paper, we describe and analyse a formative intervention with prospective high school mathematics teachers, aimed at developing their competence of didactic suitability analysis of mathematics textbook lessons. Design: The methodology followed is didactic engineering, furthermore, the content analysis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The research team is committed to reflect after each implementation in order to readapt the initially proposed design, if necessary. Thus, for the planning and design of the training experience described in this article, we relied on the retrospective analysis of interventions previously implemented with future Spanish teachers of primary education (Castillo & Burgos, 2022) and secondary education (Castillo et al, 2021(Castillo et al, , 2022c. As we show in the next section, the limitations found in those training actions were considered to improve the design and implementation of the new intervention.…”
Section: Context and Research Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The research team is committed to reflect after each implementation in order to readapt the initially proposed design, if necessary. Thus, for the planning and design of the training experience described in this article, we relied on the retrospective analysis of interventions previously implemented with future Spanish teachers of primary education (Castillo & Burgos, 2022) and secondary education (Castillo et al, 2021(Castillo et al, , 2022c. As we show in the next section, the limitations found in those training actions were considered to improve the design and implementation of the new intervention.…”
Section: Context and Research Methodologymentioning
confidence: 99%
“…In previous experimental cycles, it was observed that participants did not justify the level of compliance with each indicator in the TLAG-Proportionality (Castillo et al, 2021(Castillo et al, , 2022cCastillo & Burgos, 2022). For this reason, it was decided to include in the guide given to the PMT, in addition to the column for recording the numerical rating (0, 1, 2) of the degree of compliance with each indicator, another column in which they had to explain the reasons that had led them to assign that rating.…”
Section: Design Of the Training Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…These suitability indicators must be enriched and adapted according to the specific mathematical content to be taught (Breda et al, 2017), but also to the type of instructional medium, understanding that both constrain aspects of the different components in didactic suitability. Thus, in Castillo et al (2021), the system of didactical suitability components and indicators of Godino (2013) is revised and particularised to develop a textbook lesson analysis guide for proportionality (TLAG-Proportionality) as a tool to guide the reflection of pre-service and in-service teachers on the instructional processes planned in textbook lessons on proportionality. This guide includes specific indicators based on an exhaustive review of research results and expert judgments assumed by the academic community (Breda et al, 2017), which allow identifying didactic-mathematical knowledge to be considered in the evaluation, redesign or management of proportionality teaching processes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Some of the specific interventions developed in the field of teacher education based on the DMKC model have used the didactic competence tool, its components and indicators (Godino, 2013) to organise teachers' systematic reflection on their own practice or that of others and to develop the competence to evaluate planned or implemented instructional processes (Breda et al, 2018;Font et al, 2018;Giacomone et al, 2018;Hummes et al, 2019;Morales-López and Araya-Román, 2020;Pino-Fan et al, 2013). Some of these studies have dealt specifically with the mathematical content of proportionality (Burgos et al, 2018;Castillo et al, 2021;Esqué & Breda, 2021). Despite the longitudinal and cross-cutting importance of this content in the primary and secondary curricula, as well as being the bridge to advanced mathematical thinking, proportionality is often not adequately addressed in school mathematics textbooks at both stages (Ahl, 2016;Burgos, Castillo et al, 2020;Shield & Dole, 2013).…”
Section: Introductionmentioning
confidence: 99%